The Influence of Artificial Intelligence (Cici AI Application), Learning Independence, and Learning Environment on Office Technology Learning Outcomes: Pengaruh Penggunaan Kecerdasan Buatan (Aplikasi Cici AI), Kemandirian Belajar, dan Lingkungan Belajar terhadap Hasil Belajar Teknologi Perkantoran - Firjatullah, Jodie; Swaramarinda, Darma Rika; Febriantina, Susan (RADIANT: Journal of Applied, Social, and Education Studies, 2025)
This study examines the influence of Artificial Intelligence (AI) utilization through the Cici AI application, student learning autonomy, and the learning environment on academic performance in the Office Technology subject. While previous research has explored these variables separately, only a limited number of studies have investigated their combined effect, especially within the context of vocational education. To address this research gap, the study adopts a quantitative explanatory approach with a cross-sectional design. Data were collected from 105 students in Grades X and XI at SMKN 16 Jakarta using a structured online questionnaire. The data were analyzed using SmartPLS 4.0. The findings indicate that all three independent variables have a significant and positive impact on student learning outcomes. These results underscore the importance of integrating technological innovation, learner autonomy, and a supportive educational environment to improve academic achievement in vocational schools.